Economic Issues with Natural and Organic Beef - Boland, Michael; Boyle, Elizabeth; Lusk, Christy (My University, 1999)
This publication provides an overview of natural and organic beef in Kansas.
MF2432_1999_12
Keywords: MF2432; Economics; Livestock; MF